Preparation and electrochemical properties of Al-based composite coating electrode with Ti4O7 ceramic interlayer for electrowinning of nonferrous metals. (1st December 2019) - Han, Zhaohui; Xu, Yang; Zhou, Shenggang; Zhu, Peixian
Abstract: Electrode materials with an Al-based coating and a Ti4 O7 ceramic interlayer were prepared by plasma spraying to obtain improved electrochemical properties. RuO2 –TiO2 coatings doped with Sn, Ta and Ir, or La were prepared by thermal decomposition. The results indicate that good bonding between Al and Ti4 O7 was obtained by plasma spraying. The dopants affected the electrochemical performance by changing the surface morphology of the active coatings. The addition of Sn not only improved the electrocatalytic activity in the chlorine evolution reaction but also inhibited the electrocatalytic activity in the oxygen evolution reaction. The electric potential distribution on the surface of the electrode materials with an Al-based coating and a Ti4 O7 ceramic interlayer was more uniform than that of a Ti/RuO2 –TiO2 anode. The results of electrowinning tests revealed that an Al/Ti4 O7 /RuO2 –TiO2 –SnO2 anode exhibited the best anodic performance with lower energy consumption, a longer accelerated lifetime, more deposition of Co as a product, and greater efficiency.